Perspectives on Probiotics and Bronchopulmonary Dysplasia - Yang, Kun; Dong, Wenbin (Frontiers in Pediatrics, 2020)
Bronchopulmonary dysplasia (BPD) is a chronic respiratory disease of preterm infants, associated with high morbidity and hospitalization expenses. With the revolutionary advances in microbiological analysis technology, increasing evidence indicates that children with BPD are affected by lung microbiota dysbiosis, which may be related to the illness occurrence and progression. However, dysbiosis treatment in BPD patients has not been fully investigated. Probiotics are living microorganisms known to improve human health for their anti-inflammatory and anti-tumor effects, and particularly by balancing gut microbiota composition, which promotes gut-lung axis recovery. The aim of the present review is to examine current evidence of lung microbiota dysbiosis and explore potential applications of probiotics in BPD, which may provide new insights into treatment strategies of this disease.